Changes in children's fatigue during the course of treatment for paediatric cancer - Perdikaris, Pantelis; Merkouris, Anastasios; Patiraki, Elisabeth; Papadatou, Danai; Vasilatou-Kosmidis, Helen; Matziou, Vasiliki N. (My University, 2008)
Background: Fatigue is described as one of the most distressing symptoms of cancer therapy; yet it has received limited clinical attention. Children are suffering from a symptom that is under-diagnosed during their treatment. Aim: The aim of this study is: (a) to assess the change in fatigue scores during cancer treatment according to children's perspectives, and (b) to describe the possible causes of fatigue from children's points of view. Sample and methods: The present study is part of an ongoing prospective study. The research group consisted of 40 (n = 40) children aged 7–12 years with cancer who are being followed up in the oncology clinic of a Greek children's hospital. After parental consent was obtained, data were collected using the Child Fatigue Scale and a sociodemographic data form. Results: The children with cancer reported a statistically significant increase in fatigue scores during their treatment (F = 6.846, P = 0.003). Gender was the only demographic factor associated with a significant increase in the fatigue scores (F = 4.857, P = 0.034). Conclusions: Cancer treatment was found significantly to increase children's fatigue levels. Medical procedures and the hospital environment seemed to be major causative factors of the fatigue experienced by children with cancer during their treatment.
Keywords: Cancer; Causes; Child Fatigue Scale; Greece; Paediatric